PENGARUH PEMAHAMAN ETIKA BISNIS ISLAM TERHADAP MOTIVASI KERJA KARYAWAN DAN KUALITAS PELAYANAN KARYAWAN BANK MUAMALAT CABANG JAMBI - Muhammad Andriyansyah Yudha Gusti Wibowo (Fakultas Ekonomi dan Bisnis Islam (FEBI), Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2019)
Quality of service is very important in the business of financial services, including in it is a service business finance that is managed by sharia. One of the syariah financial institutions that do business financial services is Bank Muamalat Branch Jambi. Service quality is determined by many factors, two of which are an understanding of Islamic Business Ethics and Employee Work Motivation. This study examines the problems related to the influence of Understanding Islamic Business Ethics on Employee Motivation and Quality of Employee Services at Muamalat Bank Jambi Branch. The approach used is a quantitative approach by examining three variables, namely understanding Islamic business ethics, employee work motivation, and employee service quality.